Enhancing The Brand Awareness of Tomo Cafe Peneleh By Highlighting The Unique Selling Points in Instagram Reel - Melisa; Jusuf Imam Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This thesis explores the issue of low brand awareness faced by Tomo Cafe Peneleh, a cafe located in Surabaya that rebranded from Tomokofi. This research aims to identify the level of brand awareness and uncover the unique selling points (USPs) of the cafe, as well as the effectiveness of Instagram as a promotional tool. Data was collected through interviews with both existing customers and potential target consumers. The interviews were conducted using a structured questionnaire that had been prepared in advance using Google Forms. To ensure the accuracy of the responses, the writer directly interview the respondent and help filling up the questionnaire. Results showed that most respondents were unaware of the cafe's existence. However, the cafe’s cozy atmosphere, strategic location, and delicious drinks were frequently mentioned as its strongest USPs. To address the problem, the writer created a sample Instagram Reel designed to highlight these USPs as a tool to help them.